Alien species established in the Bay of Biscay suggest significant contribution of both fouling and dry ship compartments - Menéndez-Teleña, Deva; Soto-López, Veronica; Bartolomé, Marlene; González Arenales, Monica; Montes, Horacio J.; Ardura, Alba; Garcia-Vazquez, Eva (Frontiers in Marine Science, 2023)
Introduction The majority of studies on marine biosecurity focus on aquatic species, but invaders can also use dry ship compartments for dispersal; this pathway has been less explored than fouling or ballast water. Here we analysed the maritime traffic of the international Port of Gijon (south Bay of Biscay, Spain) as a case study. Methods Main donor countries were identified from traffic data. From the Global Invasive Species Database, we detected a similar proportion of expected global alien invasive species (AIS) from fouling and containers pathways to be actually settled in the recipient region. Results The AIS diversity transported via fouling was higher than that transported by containers. No significant difference between Australia, Brazil, Canada and South Africa in the proportion of global AIS actually transferred to Bay of Biscay supports the vision of port networks as a new ecosystem with multiple demes. Different AIS catalogues in the donor regions may explain a higher proportion of terrestrial AIS introduced via containers from Brazil and South Africa and marine AIS introduced via fouling. Discussion A more careful surveillance of biota in dry ship compartments, including it in a future revision in the International Convention for Safe Containers, is recommended to reduce the contribution of shipping to biological invasions.